ARENA SOSIAL, PETANI, DAN PERLUASAN KONFLIK PERTANAHAN DI SUMATERA UTARA - Alan Darmawan (Universitas Andalas, 2020)
This article deals with an agrarian dispute that has expanded from the ‘plantation belt’ to the swampy area on the East Coast of North Sumatra, which intertwined with a colonial legacy, environmental issue, Masyarakat Adat discourse, and recent political development. I conducted fieldwork in 2014 and periodic visits in 2015 to live among the community, observe, discuss, and document the events that occurred in the periods, and analyze them historically and also in the recent socio-political and economic context. Focussing on a community called Orang Paluh who are mostly the descendants of the ex-plantation labors in Percut residing on the marshland named Paluh Merbau, this research looks at their attempts in dealing with land grabbing, the change of land use, and in negotiating with the restriction in utilizing mangrove trees in their surroundings. In such a social arena of the dispute, Orang Paluh played multiple strategies against land grabbing through mass mobilization, legal dispute, political support from the local political elites, and an alliance with Badan Perjuangan Rakyat Penunggu Indonesia (BPRPI), which holds a mandate as a regional branch of Aliansi Masyarakat Adat Nusantara (AMAN).